Los retos actuales para las tradiciones indígenas. Procesos de transformación y reelaboración en Oaxaca - Alicia M. Barabas (Universidad Autónoma Metropolitana Unidad Iztapalapa, 2006)
PRESENT CHALLENGES FOR INDIGENOUS TRADITIONS. TRANSFORMATION PROCESSES AND RE-ELABORATION IN OAXACA. The foremost present challenges that indigenous peoples of Oaxaca are facing in order to reproduce their cultural and social traditions are the new protestant and independent religious alternatives as well as migration -specially the transnational one. This paper attempts to show the cultural and social transformations in regards to these two phenomena as well as the adaptative and re-elaborated processes of indigenous traditions.